Analisis Pengurangan Lead Time untuk Divisi Komersial dan Evaluasi Program Referral pada PT. X - Bernadus Arron Atmaja; Jani Rahardjo (Jurnal Titra, 2021)
PT. X is a company that dwelves in shipping and logistic (shiplog) business. As time go on and world change, PT. X follow the trend and released an application named mySPIL in 2017. In order to increase the userbase of mySPIL, marketing department implemented referral program in 2020. Aside from reaching to the new digital market, PT. X also wants to increase their commercial division service quality by reducing the amount of lead time for their processes. Research was done to reduce the lead time required by customer service, sales, and trade department. Research was done by identifying seven wastes, searching for root causes using five whys analysis, and mapping lead time using value stream mapping. Suggestions given to reduce wastes were deemed possible to reduce lead time on commercial division and referral program implemented by marketing department managed to create a significant difference in new relation growth for PT. X.